A histeria e a feminilidade em Elis Regina - Neves, Maria de Lourdes Turbino (2013)
This dissertation developed a study about hysteria and femininity in the light of Freudian psychoanalytic theory. It starts through the clinical observation of women considered to have hysterical neurosis with a tendency of sublimation, including a common feature, which is the ability to turn adversity into motivation for growth, for the fulfillment of wishes in the personal and professional fields. This instinctual satisfaction allows that their psyche does not succumb to a phobic or conversion symptoms and those they are socially recognized for their talent for cultural creation. Seeks to set this hysterical neurosis viewpoint, in the object of study chosen for this research work, which is the biography of Elis Regina, still one of the greatest singers in the country. The interpretations of the artist, who also explored the performing arts, yielded contributions to the role of women in the public and private sectors of the Brazilian society of the 1960s and 1970s. Elis lived a poor childhood and adolescence, but in adulthood, built a meteoric career of successes. Her life was marked by a stubborn desire to achieve your goals. The sublimatory condition which assumed allowed her to keep productive until the last days of her life, reaping the rewards of your artistic trajectory which built. This implies that their symptoms remained relegated to a secondary position